Renewable and non-renewable energy consumption and total factor productivity growth: The case of G20 countries - Neffati, Mohamed; Jbir, Rafik; Benzina, Naceur (Energy Economics Letters, 2023)
The purpose of this paper is to investigate the short and long-run relationships between renewable, non-renewable energy consumption (NREC) and economic growth. This study highlights the importance of renewable energy consumption to improve the total factor productivity (TFP) in G20 countries spanning on 2002-2018. Using the approach of panel Feasible Generalized Least Squares (PFGLS) cross-section and period weight and FGLS cross-section and period sur robust, we have divided the sample in three groups: G20, G7 and G20-G7. The findings show that there is a negative effect of Renewable Energy Consumption (REC) on TFP in G7 and a positive effect in the other groups. Our main results indicate that there is a strong significant and positive relationship between REC and TFP growth in the long run in the hull G20 countries. But, in the G7, there is a negative relationship due to the negative effect in the environment. The results of granger causality tests indicate the existence of one-way causality from NREC to TFP in G20 and G20-G7, while from TFP to NREC in G7. To boost overall productivity and maintain sustainable development, all nations must invest in renewable energy.